Do neoliberalismo ao neodesenvolvimentismo: a trajetória brasileira nas últimas duas décadas - Silva, Yasmin La Manna Marques da (2015)
Although we may affirm that Brazil is today under a stable and solid democratic regime, after two decades of an authoritarian regime, the political and economic scenario is still going through a series of transformations that define the current historical cycle of our country in the democratic period. Having this context in mind, this paper aims at reviewing the Brazilian economic policy of the last twenty years and analyzing to which extent those initiatives were influenced by the neo-liberalism and neo-developmentism. To that, beyond resuming the fundamental concepts of those theories and emphasizing its application in Brazil and Latin America, the main measures adopted by Fernando Henrique Cardoso, Luis Inácio Lula da Silva and Dilma Rousseff s governments will be presented, highlighting how neo-liberal and neo-development ideas were applied, why those measures were taken, what were the consequences of that and if they indicate continuity or rupture compared to the last government